How Very Good Small Crucibles Are Made, And Small Shells For Melting All Kinds Of Metals. (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1942)
SINCE I promised you above when speaking of the melting of metals to teach you to make small crucibles and shells for melting, I do not wish to fail in my promise. For, in truth, since they are instruments that are much used for this procedure, they increase the work if they are not good, and often cause great extra expense as well as necessitating repetition of the work. If they are good they save everything. Therefore, if you have to make them, do it so that they, are greatly aided by art. It is first necessary to have the clay of a good nature, that is, resistant to the force of the fire by its own natural virtue, either when it is lean or when its viscousness is mixed with much talc, and whether it is yellow or white. This should be well freed from small stones and beaten well with an iron, and then thoroughly mixed by hand. With this should be mixed an eighth part of finely ground and sifted iron scale,* and also some [145] young ram's-horn ashes. These things should be well mixed together by hand and by beating them. If this clay should not be strong enough by itself, it is mixed with another lean clay, with crushed peperino, flintstone, or some other stone that in your judgment seems to be arid and resistant. Crucibles are worked on a low potter's wheel turned by hand, or on a high one turned by foot, just as plates are made. Both large and small ones are made. Most of them are given a triangular shape at the mouth, and the shells have a kind of spout for ease in pouring out the metal. This done they are well dried, and baked in furnaces like pots or other vessels. At the end, when they have been thus made they are used for melts.